Reasoning web : semantic interoperability on the web : 13th International Summer School 2017, London, UK, July 7-11, 2017, Tutorial lectures /: semantic interoperability on the web : 13th International Summer School 2017, London, UK, July 7-11, 2017, Tutorial lectures. (2017) - Unknown
No abstract available